International collaboration in Brazilian science: financing and impact - McManus, Concepta (Scientometrics, 2020)
The study of international collaborations can help in understanding the benefits of such relationships and aid in developing national financing policies. In this paper, the international collaboration of Brazilian scientists was studied using SciVal(®) and Incites(®) database, looking at its effect on the universities, financing agencies and different areas of knowledge and research topic clusters. Cluster and principal component analyses of scientometric data were carried out. While the results confirmed known knowledge that international collaboration increases impact, this study shows that Brazilian researchers are contributing to prominent research topics worldwide, in all areas of knowledge. This finding is contrary to several points of view that identify Brazil as a regional and not an international partner in science. Important also to note the impact of Brazilian authors in international collaboration that is well above the world mean. The collaboration of Brazil with foreign partners brings benefits for both sides, creating the opportunity of Brazilian research access to financing from international agencies. Increases in measures of impact are also seen for both sides. Foreign partners likewise benefit from higher impact factors in the same topic cluster, when collaborating with Brazilian partners. Publishing open access in high impact journals is fundamental for maintaining Brazilian science at the forefront. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11192-020-03728-7) contains supplementary material, which is available to authorized users.